2021
DOI: 10.18178/ijiet.2021.11.10.1550
|View full text |Cite
|
Sign up to set email alerts
|

Development of a GeoGebra-Assisted Calculus Worksheet to Enhance Students’ Understanding

Abstract: The goal of this study is to develop a GeoGebra-assisted worksheet to enhance students' understanding of calculus. Many studies report that students have difficulty understanding calculus. GeoGebra provides an alternative method to overcome the difficulties associated with calculus. The Plomp development model consists of three phases: specifically, preliminary analysis, prototype development and an assessment was used in this study. The subjects of this study were 37 students. The results of this study are va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…GeoGebra-assisted worksheets on the derivative of functions of two variables which are given to students at the beginning of learning, really help students to explore features related to the topic. Thus, using GeoGebra accelerates the students' understanding on the topic discussed (Yerizon, Fatimah and Tasman, 2021). The achievements of the experimental group were generally more prominent than the control group.…”
Section: Pre-test Scores Of the Control And Experimentsmentioning
confidence: 86%
See 1 more Smart Citation
“…GeoGebra-assisted worksheets on the derivative of functions of two variables which are given to students at the beginning of learning, really help students to explore features related to the topic. Thus, using GeoGebra accelerates the students' understanding on the topic discussed (Yerizon, Fatimah and Tasman, 2021). The achievements of the experimental group were generally more prominent than the control group.…”
Section: Pre-test Scores Of the Control And Experimentsmentioning
confidence: 86%
“…In learning calculus with the topic of differential equations grouped into two groups, the score achieved by the experimental group (using GeoGebra) is a higher score compared to the control group (not using GeoGebra) (Latifi et al, 2022). The results of research on understanding calculus topics on derived sub-topics, students' understanding with the help of Geogebra is better than traditional learning models (Yerizon, Fatimah and Tasman, 2021). Furthermore, in research on teaching mathematics using GeoGebra, several researchers found that this software is able to improve understanding of mathematics (Attorps, Björk and Radic, 2016) (Saha, Ayub and Tarmizi, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…Using a strategy involving the manipulation of things, students may produce changes and gain insight into the effects those changes have on the items upon which they depend. There was a time when students learned to solve issues by actively exploring mathematical relations (Yerizon & Tasman, 2021).…”
Section: Describe Important Geogebra Software In Mathematicsmentioning
confidence: 99%
“…They also have trouble with more complicated algebra tasks like finding tangents, parallel lines, and lines that cross each other. Therefore, many students struggle with understanding calculus (Yerizon & Tasman, 2021).…”
Section: Introduce the Problemmentioning
confidence: 99%
“…Additionally, technical issues and teachers' skills in integrating technology into learning are significant challenges. The continuously evolving digital era requires teachers to have the skills to leverage technological tools for effective teaching (Ratu et al, 2022;Yerizon et al, 2021). However, not all teachers have sufficient understanding or training in this regard.…”
Section: Introductionmentioning
confidence: 99%